Hydrogen absorption kinetics and microstructural features of TiFe0.8Mn0.2 alloy - Ryun-Ho Kwak; Taeyang Kwak; Da Hye Lee; Sojin Jung; Jang-Won Kang; Seongtak Kim; Tae-Wook Na; Seok Su Sohn; Hyung-Ki Park; Taejun Ha (Journal of Materials Research and Technology)
This study investigated the microstructural features and the hydrogen absorption properties of as-cast, 10 h annealed, and 20 h annealed TiFe0.8Mn0.2 alloy samples. TiFe with the Body-Centered Cubic (BCC) B2 structure and Fe2Ti with the C14 Laves hexagonal structure were observed in the alloy samples, and the amount of precipitated second phase Fe2Ti within the TiFe matrix phase was significantly reduced in both 10 h and 20 h annealed samples. During the annealing treatment, TiFe0.8Mn0.2 alloy changes in terms of the equilibrium phase fraction and chemical composition were predicted through Thermo-Calc software calculation. When the samples were hydrogenated under 40 bar of hydrogen at 20 °C, the 20 h annealed sample absorbed 1.6 wt% H2 within the longest time among the three samples. The maximum hydrogen absorption capacities of the three samples were found to be the same, exhibiting a value of 1.81 wt% H2. Furthermore, the Scanning Electron Microscope – Electron Backscatter Diffraction (SEM-EBSD) results showed that the annealing treatment increased the grain size of the B2 matrix by decreasing the grain boundary length. The long length of the B2 grain boundary due to the small B2 grain size appeared to assist the hydrogenation of the alloy by acting as pathways for supplying hydrogen to the inside of the alloy.